2022
DOI: 10.1021/acs.jpcb.2c06315
|View full text |Cite
|
Sign up to set email alerts
|

Application of Fundamental Chemical Principles for Solvation Effects: A Unified Perspective for Interaction Patterns in Solution

Abstract: We demonstrate the utility of basic chemical principles like the "|Δμ| big is good" (DMB) rule for the study of solvation interactions between distinct solutes such as ions and solvents. The corresponding approach allows us to define relevant criteria for maximum solvation energies of ion pairs in different solvents in terms of electronegativities and chemical hardnesses. Our findings reveal that the DMB principle culminates into the strong and weak acids and bases concept as recently derived for specific ion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…In a recent paper, we were also able to show that the SWAB principles can be derived from the DMB condition. 95 Hence, one can conclude that the SWAB and the HSAB principles are closely connected to the DMB condition which is known as a cardinal reactivity principle. In summary, it can be concluded that the electronic properties of the solvent molecules as well as their polarizability play an important role for the resulting entropy values in terms of distinct ion pair solvent combinations.…”
Section: Interpretation Of Feature Importancesmentioning
confidence: 97%
“…In a recent paper, we were also able to show that the SWAB principles can be derived from the DMB condition. 95 Hence, one can conclude that the SWAB and the HSAB principles are closely connected to the DMB condition which is known as a cardinal reactivity principle. In summary, it can be concluded that the electronic properties of the solvent molecules as well as their polarizability play an important role for the resulting entropy values in terms of distinct ion pair solvent combinations.…”
Section: Interpretation Of Feature Importancesmentioning
confidence: 97%
“…In the case of the BSA-Al 3+ complex, two negative peaks with good intensities at 1656 cm −1 along with 1532 cm −1 , corresponding to the amide I and amide II, respectively were observed in the diference spectrum. Since Al 3+ is a hard acid, it might have reacted with the C�O, COO − , and NH groups of BSA, based on the Hard and Soft Acid Base (HSAB) theory of binding [8,9,22,23].…”
Section: Bsa Interaction With Group a Metal Ions (Al +3 )mentioning
confidence: 99%